Recent Advances in Stored Product Protection (Springer Berlin Heidelberg, 2018)
This book aims to assess, evaluate and critically analyze the methods that are currently available for a judicious pest management in durable food. It presents and analyzes a vast amount of methods that are already in use in "real world" industrial applications. After the phase-out of methyl bromide, but also the withdrawal of several insecticides and the continuously updated food safety regulations, there is a significant knowledge gap on the use of risk-reduced, ecologically-compatible control methods that can be used with success against stored-product insect species and related arthropods. The importance of integrated pest management (IPM) is growing, but the concept as practiced for stored products might differ from IPM as historically developed for field crops. This book discusses a wide variety of control strategies used for stored product management and describes some of the IPM components. The editors included chemical and non-chemical methods, as both are essential in IPM. They set the scene for more information regarding emerging issues in stored product protection, such as emerging, alien and invasive species as threats for global food security, as well as the importance of stored-product arthropods for human health. Finally, the analysis of the economics of stored product protection is presented, from theory to practice.